Found: the Palaeolithic of Qatar - Scott-Jackson, J; Scott-Jackson, W; al-Naimi, F (Archaeopress Publishing, 2017)
The seeming lack of evidence for a Palaeolithic presence in Qatar has been enigmatic. This has now changed. Here we report on discoveries made by the PADMAC Unit during 2013/2014 and the far-reaching implications of these findings. Our preliminary analysis of the Qatar lithic assemblages — QSS25, QSS29 (PADMAC Unit collection) and A-group Site I and A-group Site III (Kapel collection) — revealed the presence of large chopping tools and crude ‘Abbevillian’ cores, both indicative of an early stage within the lower Palaeolithic period, while the absence of classic Acheulean hand axes might even suggest a date exceeding one million years. Furthermore, the particular suite of technological traits we identified in Umm Taqa ‘B-group’ Site XXXIV (Kapel collection) lithic assemblage, are characteristic of middle–upper Palaeolithic transitional industries found in the Levant, Nile Valley, and southern Arabia. Hence, we tentatively assign the ‘Taqan’ industry to the upper Palaeolithic. Specific lithics from the QSS32 (PADMAC Unit collection) assemblage, allude to further ‘Taqan’ sites in southern Qatar.